Exploring a contemporary picturebook with young readers in the foundation phase - Makeeda N. Phekani (South African Journal of Childhood Education, 2023)
Background: Given the ongoing literacy crisis in South Africa, there is a need for teachers, as well as teacher education programmes, to explore various means to enable learners to develop reading comprehension. This study sought to examine the intricacies of a series of small group literacy activities that hinged on the in-depth and repeated engagement with a contemporary picturebook. Furthermore, it aims to evaluate whether children can develop an affinity for these books.